2015
DOI: 10.1002/jat.3219
|View full text |Cite
|
Sign up to set email alerts
|

The impact of caffeine on connexin expression in the embryonic chick cardiomyocyte micromass culture system

Abstract: Cardiomyocytes are electrically coupled by gap junctions, defined as clusters of low-resistance multisubunit transmembrane channels composed of connexins (Cxs). The expression of Cx40, Cx43 and Cx45, which are present in cardiomyocytes, is known to be developmentally regulated. This study investigates the premise that alterations in gap junction proteins are one of the mechanisms by which teratogens may act. Specifically, those molecules known to be teratogenic in humans could cause their effects via disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…The cell density was always adjusted to 3 x 106 cells/mL. Cell density of 3x106 cells/ml was used, as this was identified as optimal in previous studies [ 10 ]. Cells were seeded as 20μl drops into a 24-well plate (Nunclon, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell density was always adjusted to 3 x 106 cells/mL. Cell density of 3x106 cells/ml was used, as this was identified as optimal in previous studies [ 10 ]. Cells were seeded as 20μl drops into a 24-well plate (Nunclon, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in this laboratory have demonstrated the presence of cardiac muscle cells as opposed to skeletal muscle cells in micromass culture [ 4 ]. In addition, more detailed immunocytochemical studies in similar cultures performed by Ahir et al demonstrated the presence of predominantly cardiomyocytes and the role of connexins in the mediation of the effects of caffeine on chick cardiomyocytes in micromass culture [ 10 ]. Immunohistochemistry was used to show that cells within the chick MM culture employed in this study primarily yielded cardiomyocytes, showing positive staining for cardiac-specific α- and β-myosin heavy chains and cardiac troponin T antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…RyRs may modulate gap junction formation during stress and aging. The pan RyR activator caffeine decreased the expression of gap junction forming proteins, the connexins Cx40, Cx43, and Cx45, and reduced the contractility of cardiomyocytes [74]. These effects have been attributed to long-lasting activated ryanodine receptors by caffeine.…”
Section: Ryanodine Receptorsmentioning
confidence: 99%